Sleep abnormalities in traumatic apallic syndrome. Issue 4 (April 1995) - Giubilei, F; Formisano, R; Fiorini, M; Vitale, A; Faroni, J; Toni, D; Santilli, V
Abstract : Sleep patterns in 10 patients with traumatic apallic syndrome were studied, together with 10 healthy controls matched for sex and age. All patients underwent neurological examination, brain CT, and polysomnographic recording within six months (mean 99 (SD 45) range 47-180 days) from the onset of symptoms. Clinical follow up was performed six months after enrollment in the study. Sleep patterns were recorded in nine out of 10 patients. In the tenth patient there was no rhythm resembling physiological sleep. This patient was the only one who remained in a persistent vegetative state and died before the six month follow up. The severity of neurological deficit at follow up was significantly related to the duration of coma. There was no significant difference between patients and controls with respect to sleep architecture. The time spent awake after sleep onset was longer in patients than controls. Our data highlight the presence of sleep fragmentation in traumatic apallic syndrome, which might be due to changes in brain structures responsible for sleep maintenance. The absence of sleep-wake cycles might indicate a poor outcome.